Comparison of the Safety and Efficacy of Laparoscopic Left Lateral Hepatectomy and Open Left Lateral Hepatectomy for Hepatolithiasis: A Meta-Analysis - Wang, Xiaoji; Chen, Ai; Fu, Qiurong; Cai, Chunping (Frontiers in Surgery, 2021)
Background: Intrahepatic duct (IHD) stones, also known as hepatolithiasis, refer to any intrahepatic stones of left and right hepatic ducts. It is a benign biliary tract disease with high recurrence rate, many complications and difficulty in radical cure. The aim of this review and meta-analysis was to compare the safety and efficacy of laparoscopic left lateral hepatectomy (LLLH) and open left lateral hepatectomy (OLLH) for IHD stones. Methods: Pubmed, Embase, Cochrane, WangFang Data and China National Knowledge Infrastructure were searched for randomized controlled trials (RCTs) regarding the comparison of LLLH and OLLH in the treatment of hepatolithiasis. Standard mean difference (SMD), odds ratio (OR) and 95% confidence interval (CI) were calculated using random-effects model or fixed-effects model according to the heterogeneity between studies. Results: From January 01, 2001 to May 30, 2021, 1056 articles were retrieved, but only 13 articles were finally included for meta-analysis. The results showed that compared with the OLLH group, LLLH resulted in smaller surgical incision, less intraoperative blood loss, faster postoperative recovery, and fewer postoperative complications (surgical incision: SMD = -3.76, 95% CI: -5.40, -2.12; intraoperative blood loss: SMD = -0.95, 95% CI: -1.69, -0.21; length of hospital stay: SMD = -1.56, 95% CI: -2.37, -0.75; postoperative complications: OR = 0.45, 95% CI: 0.26, 0.78). Conclusions: In the treatment of hepatolithiasis, compared with OLLH, LLLH has the advantages of less intraoperative blood loss, smaller incision, less postoperative complications, shorter hospital stay, shorter time to first postoperative exhaust and postoperative ambulation, and rapid postoperative recovery.